A distribuição dos cursos UAB em Minas Gerais: análise e proposta de intervenção - Ribeiro, Natália Niquini (2019)
This dissertation proposes to map all the courses offered by the Open University of Brazil (UAB) in the on site support poles of the State of Minas Gerais, with the objective of analyzing the distribution of these cours es in the State and identifying the possible impacts of this distribution. At first, a bibliographic review is made in which the historical comprehension and the concepts of Distance Education (EaD), the Brazilian legislation and the UAB, with their object ives and functioning, including the characterization of the present support poles are addressed. Soon after, the Public Higher Education Institutions (IPES) will be held, responsible for offering the UAB System courses in the country, considering their dec entralized responsibility, highlighting the public institutions, conceptions about the theme, their particularities and challenges. Next, and based on CAPES Ordinance No. 218 of September 24 TH , 2018, which regulates the admissibility guidelines for new UAB centers, an analysis is made to assess the impacts of this distribution on the results of the UAB Program, considering the guidelines established in the legal documents and government programs for the institutionalization of EaD with the focus on meeting the arrangements of vocational training policies for certain social groups. At the end, this paper present s a proposal for intervention for better UAB results as a public policy, with the adoption of criteria in the installation of new courses in the UAB p oles of the state, and may even serve as a model for this government educational policy at national level.